Limits Of Parental Interference In Children's Household Reviewed From Law No. 1 Of 1974 - Naufal Ikhtiar (International Journal of Sharia Studies, 2024)
In the household life of the father and mother also have an influence on the household of their children. In this paper based on the literature data that the author obtained that in Law No. 1 of 1974 article 45 that parents are not required to interfere in the household affairs of children until the child asks for it. This study is a type of library research with the aim of identifying problems (Problem Identification) and is explanatory (explaining) by testing the correlation between variables as cause and effect. The results of the study indicate that parents do not have the right to interfere in the household affairs of their children in order to maintain the welfare of the child's household itself. Because the facts in the field, the child's household is not harmonious and even divorced because parents interfere too much in the household affairs of their children.